The Impact of Productive Zakat on the Income Inequality of Mustahiq in Yogyakarta - Darsono, Susilo Nur Aji Cokro; Raihana, Mitha; Jati, Hafsah Fajar; Pachmi, Anisya (Program Studi Ekonomi FEB UMY, 2019)
Inequality in income distribution is one of the economy problems that faced by most developing countries, including Indonesia. In order to reduce the income gap, Islam proposes instruments to solve this problem, such as Zakat. This is not only an obligation for the Muslim but it also has the goal of improving the economy conditions in society. There is the movement of wealth from high income society to low income society in zakat, so the income will not be concentrated in a certain society. Zakat distribution can support the achievement one of the Sustainable Development Goals (SDGs), namely goal 10, which is to reduce inequalities. This research aims to analyze the effect of productive zakat on reducing income inequality among mustahiq or zakat recipients. A survey employing a questionnaire was applied in this research to find the data from mustahiq population in Yogyakarta City. Lorenz curve, Gini ratio index and World Bank inequality criteria were applied to analyze the inequality of income distribution. This research found that distribution of productive zakat decreased the inequality of income among mustahiq as shown by the decreasing area in the Lorenz curve. In addition, the Gini ratio also fell from 0.37 to 0.30 which shows the decrease in income inequality among mustahiq. Finally, the proportion of income in 40% low income society increased from 16.83% to 21.04%.